The Development of Plant E-Atlas for Acid-Base Test Indicators as Supporting Teaching Materials During the Covid-19 Pandemic - Putri, Raddina Aprilia; Susantini, Endang; Taufikurohmah, Titik (Jurnal Pendidikan MIPA, 2021)
This research is a type of research and development. Plant E-Atlas for Acid –Base Test Indicators was developed with the aim of being used as interactive teaching material especially in the online learning process during the Covid-19 pandemic. The E-Atlas development procedure uses the Dick and Carrey model. Eligibility Levels of the E-Atlas are evaluated based on the assessment of experts and field practitioners. The effectiveness of the practicality of the E-Atlas is analyzed based on the responses of the E-Atlas users. The respondents were students at the grade X SMK Kesehatan Yannas Husada Bangkalan SMK. The average feasibility score of the E-Atlas is 90.18% with very valid criteria and 89.08% with reliable criteria. Practicality of the E-Atlas obtained an average score of 86.10%. The results of research and development of the E-Atlas show that the E-Atlas designed can be used to support online learning. In addition, the results of the assessments of experts, educational practitioners, and respondents show that the E-Atlas contains content to train Scientific Reasoning Skill. Keywords: Plant E-Atlas, online learning, scientific reasoning DOI:http://dx.doi.org/10.23960/jpmipa/v22i1.pp35-44